Positional Number System - Jha , Anil Chandra (NUTA Journal, 2020)
In a positional number system, the numerical value of each symbol depends on its position in the sequence of digits representing the number. Any integer greater than 1 may serve as a base, and in a base b system there are b digits represented conventionally by the digits 0,1,2,..., b-1. In this paper we introduce the following four positional number systems: decimal (base-10), binary (base-2), Octal (base-8) and hexadecimal (base-16). We focus on representations of these number systems together with arithmetical operations defined on them. The study of this paper ends with the conversions of number from one system into another with examples.